ANALYSIS OF GAME-BASED ACTIVITIES AND DRAMATIC PLAY EFFECTS ON PRE-SCHOOLERS’ EXECUTIVE FUNCTIONING - Mabekoje, Sesan Olatunde (Indonesian Journal of Elementary Teachers Education, 2024)
Executive function are mental skills that includes flexible thinking, working memory, and self-control needed daily to learn, work, and manage daily life. This study evaluates a comparative analysis of game-based activities and dramatic play effects on executive functioning among pre-school children. A pre-test, post-test, and control group quasi-experimental research design was used in this work. The study included a sample of eighty (80) pre-schoolers from public and private schools in six local government areas of the Ogun East Senatorial District, ranging in age from five to six years. For six weeks, each group had intervention meetings. Data were gathered using Dawson and Guare's (2010) Executive Function Skills Questionnaire for Children (Preschool and Kindergarten Version). Data were analysed using a One-way ANCOVA with results tested at .0 level of significance. Findings revealed among others, that game-based activities and dramatic play intervention had similar effects on executive functioning of pre-school children (F(1, 79) = 2.265; p > .05). The study concluded that both intervention strategies are effective in the improvement of pre-school children executive functioning.